Acute decompensated heart failure in the emergency department: Identification of early predictors of outcome. Issue 27 (July 2017) - Castello, Luigi Mario; Molinari, Luca; Renghi, Alessandra; Peruzzi, Elena; Capponi, Andrea; Avanzi, Gian Carlo; Pirisi, Mario
Abstract : Abstract: Identification of clinical factors that can predict mortality and hospital early readmission in acute decompensated heart failure (ADHF) patients can help emergency department (ED) physician optimize the care-path and resource utilization. We conducted a retrospective observational study of 530 ADHF patients evaluated in the ED of an Italian academic hospital in 2013. Median age was 82 years, females were 55%; 31.1% of patients were discharged directly from the ED (12.5% after short staying in the observation unit), while 68.9% were admitted to a hospital ward (58.3% directly from the ED and 10.6% after a short observation). At 30 days, readmission rate was 17.7% while crude mortality rate was 9.4%; this latter was higher in patients admitted to a hospital ward in comparison to those who were discharged directly from the ED (12.6% vs. 2.4%, P  < .001). Thirty-day mortality was significantly related to older age, higher triage priority, lower mean blood pressure (MBP), and lower pulse oxygen saturation (POS). At 180 days, crude mortality rate was 23.2%, higher in admitted patients compared with discharged ones (29.6% vs. 9.1%, P  < .001) and was significantly related to older age, higher serum creatinine, and lower MBP and POS. At 12 and 22 months, crude mortality rates resulted 30.4% and 45.1%, respectively. Simple and objective parameters, such as age ⩽82 years, MBP > 104 mm Hg, POS > 94%, may guide the ED physician to identify low-risk patients who can be safely discharged directly from the emergency room or after observation unit stay.